PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION DENGAN BERBANTUAN MEDIA DIRGAM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Yuli Wantika (STKIP Subang, 2023)
This research is motivated by the results of the reading comprehension ability of class VI students who are still low. This is evidenced by the results of students' reading comprehension ability which are still below the Minimum Completeness Criteria (KKM). One of the learning methods set to overcome this problem is the CIRC method. The purpose of this study was to determine the increase in students' reading comprehension skills through the CIRC learning model. This type of research is Classroom Action Research (CAR) using the Kemmis McTaggart model, which consists of four stages, namely planning, implementing, observing, and reflecting. The research data showed an increase in the average test results and an increase in the number of students who achieved the KKM in each cycle. The average score in cycle I was 74.70 with 64.70% completeness and the average score in cycle II was 81.23% with 82.36% completeness.